Optimasi Daftar Bahan Makanan Untuk Pasien Rawat Jalan dan Keluarga Menggunakan Algoritme Genetika - Istiana Rachmi; Imam Cholissodin; Marji Marji (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
The consumption of Indonesian society tend to be less healthy which resulted in various diseases. High cholesterol disease and hypertension have a high proportion rate. Both of diseases can be treat with hospitalization and outpatient. Outpatient costs are cheaper than hospitalization. But to regulate the consumption patterns of the patient's food is still difficult because of lack of knowledge. Techniques that can be used to by using genetic algorithms. The data used in this case were 137 foodstuffs grouped into sources of carbohydrates, animal protein, vegetable protein, vegetables, fruits, grease, milk and sugar. In the process of genetic algorithm using representation of integer permutation based on food index with chromosome length 168, crossover method with extended intermediate, mutation method with exchange mutation, and selection method with elitism selection. After conducting the test, the optimum parameters produced are the population size of 80 individuals, the value of cr = 0.3 and mr = 0.7 and generation 100. The final result is food for breakfast, lunch and night for seven days with nutritional content Which suits the nutritional needs of all family members, varied foodstuffs and budget-appropriate costs.